Perencanaan dan Pemilihan Supplier (Studi Kasus: PT. Nusantara Lestari Ceria Pratama) - Kevin Johnson; Ahmad Ahmad (JURNAL TEKNIK INDUSTRI, 2018)
PT. Nusantara Lestari Ceria Pratama is a company engaged in printing industry. Based on the results of the survey in the field, the company has yet to have a method that is specialized in raw material inventory planning and a good supplier selection for company. the problems that exist in the company, especially in raw material inventory is excess stocks of raw material, and for supplier selection company ofthen get quality raw materials which are not in accordance with corporate standards, frequent delays in delivery and quantity of which do not correspond to the amount ordered. In planning stockpile raw materials starts with doing a sales forecast based on historical data by the method of SES, DES, DMA, Regresi Linear, and Siklik. For reading book product selected forecasting method is SES 0,1 and for the study book product there SES 0,9. Then perform the aggregate, disgregat planning, calculation of lot sizing and application of Material Requirement Planning (MRP). With MRP applied then purchases of raw materials are more appropriate. Lot sizing calculation is the method of Least Unit Cost (LUC) yields the total cost of the inventory is low compared to most other methods. There are 4 criteria in the selection of suppliers in PT Nusantara Lestari Cheerful Pratama i.e. price, quality, service, and on time delivery. Based on the results of research that the raw material of paper Art Carton choose supplier D, raw materials paper Bookpaper choose supplier A, the raw material of paper hvs choose supplier A, glue choose supplier C, plat choose suppliers A plate, ink choose supplier B.